THE ESSENCE OF REMUNERATION FEASIBILITY IN AN EFFORT FOR THE WELFARE OF THE WORKER - Zulkarnain Ibrahim (Faculty of Law, Universitas Jenderal Soedirman, 2016)
The Remuneration feasibility is one of workers’ fundamental principle, must be implemented in national development program on employment by setting policy of composing planning labor, employment information, and job training. Professional workers will increase the productivity and company profit. Positive impact to workers, will receive their right for reasonable wages, so that reached welfare for them and their family, and live honorably and dignified in society.Key words: law, workers,reasonable wages